2017
DOI: 10.18632/oncotarget.19710
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein induces mtDNA damages, mitochondrial fission and mitophagy in human lung cells

Abstract: Acrolein (Acr), a highly reactive unsaturated aldehyde, can cause various lung diseases including asthma, chronic obstructive pulmonary disease (COPD), and lung cancer. We have found that Acr can damage not only genomic DNA but also DNA repair proteins causing repair dysfunction and enhancing cells’ mutational susceptibility. While these effects may account for Acr lung carcinogenicity, the mechanisms by which Acr induces lung diseases other than cancer are unclear. In this study, we found that Acr induces dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 65 publications
1
45
0
Order By: Relevance
“…Several DNA-damaging agents were shown to initiate autophagy [67,68] and mitophagy [69] to remove damaged macromolecules or organelles including mitochondria, which prompted us to explore if UVB and PARPi-induced mitochondrial biogenesis and morphological changes of mitochondria affects autophagy or mitophagy. We used dual labelling of Mitotracker CMxROS to stain mitochondria and microtubule-associated proteins 1A/1B light chain 3B (LC3A/B) antibody to detect autophagosomes.…”
Section: Parp Inhibition and Uvb Induces Bulk Autophagy But Not Mitopmentioning
confidence: 99%
See 1 more Smart Citation
“…Several DNA-damaging agents were shown to initiate autophagy [67,68] and mitophagy [69] to remove damaged macromolecules or organelles including mitochondria, which prompted us to explore if UVB and PARPi-induced mitochondrial biogenesis and morphological changes of mitochondria affects autophagy or mitophagy. We used dual labelling of Mitotracker CMxROS to stain mitochondria and microtubule-associated proteins 1A/1B light chain 3B (LC3A/B) antibody to detect autophagosomes.…”
Section: Parp Inhibition and Uvb Induces Bulk Autophagy But Not Mitopmentioning
confidence: 99%
“…Furthermore, a dose-dependent mitochondrial elongation was observed after UVB and PARP inhibition in Figure 4A,B indicating mitochondrial fusion. Since fused mitochondria are protected from mitophagy [76], and mitophagy-coupled elimination of mitochondria is usually preceded by fission [69] and decline in mitochondrial function [77], the here experienced induction in autophagy is considered as general autophagy and suggest that mitochondrial morphological rearrangements induced by UVB and PARPi may interfere with the initiation of mitophagy.…”
Section: Parp Inhibition and Uvb Induces Bulk Autophagy But Not Mitopmentioning
confidence: 99%
“…revealed that acrolein promotes mitochondrial ROS over-production, resulting in the formation of the mtDNA 4977 and also depletion of mtDNA content in human lung cells. 74…”
Section: The Endogenous and Exogenous Source Of The Mtdna4977 Formationmentioning
confidence: 99%
“…In Parkin-mediated mitophagy, the depolarized mitochondria stabilize phosphatase and tensin homologue (PTEN)-induced putative kinase 1 (PINK1) on the outer mitochondrial membrane, which subsequently recruits the E3 ubiquitin ligase Parkin to initiate the autophagic degradation of damaged mitochondria [11,12]. Although most studies on Parkin-dependent mitophagy have been related to neurodegenerative diseases (e.g., Parkinson's disease) [8,13], a previous study found that mitophagy acts as an important modulator in human pulmonary diseases and could represent a potential therapeutic target [14][15][16]. Therefore, we investigated the role of Parkin-dependent mitophagy as a protective mechanism against mitochondria-dependent apoptosis in LPS-induced ARDS.…”
Section: Introductionmentioning
confidence: 99%